Intrinsic Square Function Characterizations of Several Hardy-Type Spaces — A Survey (Analysis in Theory and Applications, 2022)
In this article, the authors give a survey about the recent developments of intrinsic square function characterizations and their applications on several Hardy-type spaces, including (weak) Musielak-Orlicz Hardy spaces, variable (weak) Hardy spaces, and Hardy spaces associated with ball quasi-Banach function spaces. The authors also present some open problems.
Keywords: Intrinsic square function; (weak) Musielak-Orlicz Hardy space; variable (weak) Hardy space; ball quasi-Banach function space; Campanato space.